2023
DOI: 10.1038/s41598-023-35277-3
|View full text |Cite
|
Sign up to set email alerts
|

The impact of birth weight, birth order, birth asphyxia, and colostrum intake per se on growth and immunity of the suckling piglets

Abstract: Colostrum is the only source of passive immunity and the major source of nutrients and is crucial for thermoregulation of newborn piglets in their early life. However, the amount of colostrum obtained by each piglet [colostrum intake (CI)] differs considerably in large litters as born by contemporary hyperprolific sow lines. This experiment aimed to investigate the impact of the following individual characteristics of piglets; birth weight, birth order and neonatal asphyxia at birth on CI, and further to deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 41 publications
2
5
0
1
Order By: Relevance
“…Increased litter size has been a goal of genetic selection progress in the last decades and, according to recent evaluations, it can continue to be a strategic goal in pig genetic improvement programs because the negative effects on preweaning mortality of piglets can be controlled [1]. The possible negative impacts on the mean weight of the piglets can be also problematic because lighter piglets have low survival rates [28][29][30] and, due to the positive relationship between birth weight and weaning weight [30][31][32], piglets could be weaned with less body weight, resulting in augmented difficulties to cope the weaning transaction challenges [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…Increased litter size has been a goal of genetic selection progress in the last decades and, according to recent evaluations, it can continue to be a strategic goal in pig genetic improvement programs because the negative effects on preweaning mortality of piglets can be controlled [1]. The possible negative impacts on the mean weight of the piglets can be also problematic because lighter piglets have low survival rates [28][29][30] and, due to the positive relationship between birth weight and weaning weight [30][31][32], piglets could be weaned with less body weight, resulting in augmented difficulties to cope the weaning transaction challenges [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…Для удовлетворения потребностей мясного рынка необходимо обеспечить здоровый биологический материал для откорма с хорошими производственными показателями по конверсии корма, достигнутых приростов и получаемого качества туши (de Vries H and Smidt H, 2020). Кроме того, для выращивания молодняка на свинину (Vodolazska D et al, 2023) необходимо его непрерывное производство, но в обоих случаях требуется использовать биологический потенциал воспроизводительной способности свиноматок, а интервал между опоросом и подтверждённой супоросностью должен быть минимально возможным в биологических пределах. Этот процесс при интенсивном производстве свинины невозможен, если:…”
Section: результаты и обсуждениеunclassified
“…In addition, it was reported that commensal bacteria from milk are key actors during the early stage of neonatal gut colonization, being major regulators of the host's immune responses (Stewart et al, 2018). Newborn piglets suckle the sow and rely on the nutrients ingested with milk until weaning (Vodolazska et al, 2023). In general, weaning is performed in piglets around 3-4 weeks when the feeding changes from milk to solid feed.…”
Section: Introductionmentioning
confidence: 99%